Changing denotations of selected Slovenian choronyms - Geršič, Matjaž (Acta geographica Slovenica, 2017)
This article discusses changes in the territory identified by individual choronyms, or regional toponyms. The most frequent choronyms listed by respondents include the names of Austria-Hungarian lands and their parts, which in the past referred to precisely delineated administrative units. Today their borders are largely impossible to define, but they can be determined using cognitive maps and geographic information systems. The findings presented in this article show that the denotation of these names has changed over time and that in the case of informal names it is not clearly defined.